The new records of lichenicolous fungi from Ukrainian Carpathians (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Three species of lichenicolous fungi are for first time reported in Ukraine from Chornohora Mountain Range. These are Arthonia subvarians, Didymocyrtis melanelixiae and Polycoccum umbilicariae. A. subvarians is the poorly known European species, characterized by slightly convex arthonioid ascomata, green-brown epithecium, hyaline to olive hymenium, K+ wine-red, clavate (4–)8-spored bitunicate asci and hyaline 1-septate soleiform ascospore. This species, together with Cercidospora epipolytropa and Intralichen baccisporus, grows on apothecia of Lecanora polytropa and produces dark necrotic spots on host. The taxonomic discussion and comparison with A. apotheciorum are provided. Didymocyrtis melanelixiae is characterized by immersed black globose conidiomata, ampuliform conidiogenous cells and broadly ellipsoid аseptate 1–2-guttulate hyaline conidia. It grows on thallus of Platismatia glauca together with Lichenoconium erodens and produces dark necrotic spots with the black edge. Polycoccum umbilicariae is the rarely reported species, characterized by black immersed to semi-immersed globous ascomata, hymenium without hamathecial filaments, clavate (4–)8-spored fisitunicate asci and olive to dark-brown ellipsoid (0–)1-septate smooth-walled ascospore. It growth on thallus of Umbilicaria cylindrica and produces decolorized spots with destroyed upper cortex. U. cylindrica is a new host species for Polycoccum umbilicariae. The discussion about current taxonomic position and comparison with the specimens of same species growing on another hosts are presented. Description, list of host lichens species, data about distribution in Ukraine and examined specimens are provided for each species.
Keywords: Arthonia subvarians, Didymocyrtis melanelixiae, Polycoccum umbilicariae, Chornohora Mountain Range.